Faster multicollisions attack on sponge construction - Hammad B.T.; Jamil N.; Zaba M.R.; Rusli M.E.; Ahmed I.T. (American Scientific Publishers, 2023)
Multicollision attacks are sophisticated attacks that are analyzed in cryptographic hash functions. Previous works on multicollision have reported that the technique of determining the t-collisions where t > 2 is no more difficult than that of identifying the 2-collisions. Kelsey and Schneier have improved the technique by using a fixed point to locate the multicollision with the complexity of 3.2n/2. Aumasson has developed a new attack known as the faster multicollision based on the Kelsey and Schneier attacks and implemented it in the Merkle-Damgrd construction with a complexity of 2n/2. However, this technique has never been applied to the sponge construction. In this paper, a recent multicollision attack is applied on sponge construction and we found that the sponge construction has no resistance against such attacks when c = n. 2017 American Scientific Publishers All rights reserved.